Karakteristik Aliran Darah pada Katup Semilunar Aorta Anjing Kampung yang Dinilai dengan Pulsed Wave Doppler Ekhokardiografi (CHARACTERISTICS OF BLOOD FLOW IN SEMILUNAR AORTA VALVE OF MONGREL DOG ASSESSED BY PULSED WAVE DOPPLER ECHOCARDIOGRAPHY) - Noviana, Deni; Alham, Fitri (Jurnal Veteriner; Vol 13 No 1 (2012), 2012)
The purpose of this study was to determine the characteristics of blood flow which passed through theaortic valve of normal Indonesian mongrel dogs using trans-thoracic Pulsed Wave Doppler (PWD)echocardiography. Eight (8) adult dogs (three male dogs and 5 female dogs) with an average age 3.31 ± 0.59years and average body weight 12.45 ± 1.30 kg were used in the study. Trans-thoracic PWD echocardiographyexaminations were performed in conscious/unsedated animals at the left lateral recumbence position. Theinstruments used in this study were: i) two dimensional ultrasound device and ii) phased array transducersmall foot print with 3.7 – 5.0 MHz frequency. Six elements of PWD were measured: i) heart rate (HR); ii)peak velocity (Vpeak); iii) velocity time integral (VTI); iv) mean pressure gradient (MPG); v) pulsatilityindex (PI); and vi) ratio of systole-diastole (S/D). Results showed the typically characteristics of blood flowin semilunar aorta valve is demonstrated by the only one peak wave (peak velocity = Vpeak) upon examinationby placing the Doppler scan volume right on the aorta valve. In general, all six elements of PWD measuredwere found to be higher in female dogs compared to male dogs. However, these differences were notstatistically significant (P>0.05).
Keywords: blood flow, semilunar aorta valve, pulsed wave Doppler echokardiography, mongrel dog